1876 Ala. Code 883 - (:unkn) unknown (My University, 1873)
§ 4110: Prohibited the concealed carrying of any brass knuckles, slungshots, or " other weapon of like kind or description." Punishable by a fine of $20-200 and imprisonment or term of hard labor not to exceed 6 months.
Keywords: CARRY - CONCEALED - NON-GUN ARMS